PENGARUH PROMOSI TERHADAP LOYALITAS KONSUMEN PADA JASA TRANSPORTASI OJEK ONLINE GRAB DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI - Meola, Sunday (Universitas Slamet Riyadi, 2020)
This research aims to determine the effect of promotion on consumer loyalty mediated by customer satisfaction. This research was conducted on Grab's online motorcycle transportation service. The type of data is qualitative and quantitative data. The data sources are primary and secondary data. The data collection techniques are questionnaires and literature study. The population is unlimited, so the Paul Leedy formula is used to determine the number of samples. This research used 100 people as the samples. This research shows that promotion and customer satisfaction have a significant effect on consumer loyalty, promotion also has a significant effect on consumer loyalty which is mediated by customer satisfaction.Keywords: Promotion, Customer Satisfaction and Consumer Loyalty